Are Wages in the Czech Republic and Poland Equal? - Marek, Lubos; Vrabec, Michal (Wydawnictwo Uniwersytetu Ekonomicznego we Wrocławiu, 2017)
One of the most watched characteristics used in economics and statistics is the wage. Every employee is interested in its value. It is interesting to compare one's own wages with those of others, or with the effects of other economic changes. Is my real wage rising or falling? Can I buy more this year than last year? Comparison with other countries is also interesting. For these reasons, we will try in this article to compare wages and their development during the most recent few years in the Czech Republic and Poland. Because each country has a different currency and inflation rate, we will have to convert the wages to the same currency (EUR) for the same periods, and adjust our data to eliminate the inflation. We will also be interested in the time evolution. We have reviewed this evolution with respect to the basic characteristics (growth rate and the average absolute increment) and we have also compared the trends. The classical decomposition of time series has been used to model these trends. Our output is formulated in the form of tables and charts created in MS Excel. The data sources are taken from the publications by the statistical offices of both countries and Eurostat
20-th AMSE. Applications of Mathematics and Statistics in Economics. International Scientific Conference: Szklarska Poręba, 30 August- 3 September 2017. Conference Proceedings Full Text Papers, s. 307-318
Keywords: wage; real wage; inflation; trend; statistical characteristic